COVID-19 vaccine booster dose hesitancy among key groups: A cross-sectional study - Min Huang; Rongfang He; Qi Chen; Jianying Song; Houqiang Huang; Silin Zheng (Taylor & Francis Group, 2023)
Vaccination is an important tool for controlling the spread of coronavirus disease. Notably, it is important to achieve higher vaccine booster coverage across key groups - including front-line workers who could be exposed to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and those who live and work in crowded places - to prevent or reduce the risk of severe infection and poor disease outcomes. The purpose of the study was to understand the COVID-19 vaccine booster hesitancy among key groups in Luzhou, China, to analyze its influencing factors, and to provide scientific basis and theoretical guidance for the implementation of targeted intervention. Guided by the "3Cs" model, a self-designed questionnaire was prepared through a literature search using the Delphi method. All questionnaires were completed online through a QR code. Among the 548 participants, 173 had vaccine hesitation, accounting for 31.6%. Indeed, the scores for perceived safety, expected vaccine effectiveness, and trust in the vaccine delivery system were all lower in the hesitance group than in the non-hesitance group. However, the scores for low necessity were higher in the hesitance group. The factors influencing booster hesitancy were examined, and the probability of hesitancy decreased by 72.2% and 62.5% for every 1-point increase in the confidence and safety scores, respectively. Meanwhile, the probability of hesitancy increased by 25.8% for every 1-point increase in the low necessity score. Although the COVID-19 vaccine booster hesitancy reported in the study was relatively low, a large gap remains in the willingness to receive COVID-19 vaccination in China. Therefore, the state and relevant departments should take targeted measures to help reduce vaccine hesitancy among the public and enable smooth progress in the large-scale COVID-19 vaccine booster campaign in the future.